Methylation of CIITA promoter IV causes loss of HLA-II inducibility by IFN-γ in promyelocytic cells - De Lerma Barbaro, Andrea (Oxford University Press, 2008)
The human promyelocytic cell line THP-1 expresses high level of HLA class II (HLA-II) molecules after IFN-γ treatment. Here, we report a variant of THP-1 that does not express HLA-II after IFN-γ. The variant's HLA-II phenotype is constant over time in culture and it is not related to a defective IFN-γ-signalling pathway. Transfection of CIITA, the HLA-II transcriptional activator, under the control of a cytomegalovirus promoter rescues high level of HLA-DR surface expression in the variant indicating that the biosynthetic block resides in the expression of CIITA and not in the CIITA-dependent transactivation of the HLA-II promoters. Treatment of the variant with 5-azacytidine (5-aza), which inhibits CpG methylation, restores inducibility of HLA-II by IFN-γ both at transcriptional and phenotypic level and antigen presenting and processing function of the variant. DNA studies demonstrate that the molecular defect of the THP-1 variant originates from the methylation of the CIITA promoter IV. Furthermore, treatment with 5-aza produces a substantial demethylation of CIITA promoter IV and a significant increase of IFN-γ-dependent HLA-II expression in another myelomonocytic cell line, U937. Therefore hyper-methylation of CIITA promoter IV may be a relevant mechanism of epigenetic control preventing HLA-II IFN-γ inducibility in the myelomonocytic cell lineage.